HARMONISASI REGULASI DALAM PENGEMBANGAN HUKUM EKONOMI NASIONAL: UPAYA MEWUJUDKAN KEPASTIAN HUKUM DAN PERTUMBUHAN EKONOMI INKLUSIF BERDASARKAN NILAI-NILAI PANCASILA DAN UUD 1945 - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study examines the role of regulatory harmonisation in the development of national economic law as a strategic effort to create legal certainty and promote inclusive economic growth in Indonesia. Through a literature review, the study examines how regulatory harmonisation can overcome the disharmony and overlap of regulations that have been obstacles to the implementation of economic law. Harmonisation based on the values of Pancasila and the provisions of the 1945 Constitution is expected to create a consistent and fair legal system, which in turn supports equitable development and people's welfare. The findings of the study show that regulatory harmonisation is not only important to ensure legal certainty for economic actors and investors, but also an effective means of realising an inclusive and socially just economy in accordance with the fundamental values of the Indonesian nation. Policy recommendations are formulated based on a comprehensive analysis of the philosophical, constitutional and practical aspects of regulatory harmonisation in the context of national economic law.